Theory of Three-Dimensional Nanocrescent Light Harvesters - Wiener, Aeneas (2015)
The optical properties of three-dimensional crescent-shaped gold nanoparticles are studied using a transformation optics methodology. The polarization insensitive, highly efficient, and tunable light harvesting ability of singular nanocrescents is demonstrated. We extend our approach to more realistic blunt nanostructures, showing the robustness of their plasmonic performance against geometric imperfections. Finally, we provide analytical and numerical insights into the sensitivity of the device to radiative losses and nonlocal effects. Our theoretical findings reveal an underlying relation between structural bluntness and spatial dispersion in this particular nanoparticle configuration.